Flow Cytometric Analysis of the Cytotoxic T-Cell Recall Response to Theileria parva in Cattle Following Vaccination by the Infection and Treatment Method - Mahmoud M. Elnaggar; Donald P. Knowles; William C. Davis; Lindsay M. Fry (Veterinary Sciences, 2021)
The apicomplexan hemoparasite, Theileria parva, causes East Coast fever (ECF), a frequently fatal disease of African cattle. Vaccine development has been impeded by incomplete understanding of protective immunity following natural exposure or the infection and treatment method (ITM) of immunization. This is attributable to a paucity of methods to characterize the memory T-cell repertoire following infection. To overcome this impediment, assays developed to study the immune response to other intracellular pathogens were adapted for use in studies with T. parva to enable definition of the phenotype and function of effector T cells in T. parva-immune cattle, facilitating vaccine development. As reported herein, stimulation of peripheral blood mononuclear cells (PBMC) from ITM-immunized steers with irradiated, autologous, T. parva-infected cell lines elicited a proliferative recall response comprised of CD45R0+/CCR7− CD4+ and CD8+ T cells. Subsequent co-incubation of stimulated cultures with infected cells demonstrated the presence of cytotoxic T cells (CTLs) with the ability to kill infected cells. Comparison of CTL activity in cultures depleted of CD4+ or CD8+ T cells demonstrated CTL activity was primarily attributed to CD8+ T cells. Importantly, stimulation of PBMC from vaccinated steers always elicited proliferation of CD4+ and CD8+ T cells. This was the first important observation obtained from the use of the assay described herein.